2023
DOI: 10.1001/jamanetworkopen.2023.13017
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes in Patients With Hormone Receptor–Positive Metastatic Breast Cancer With Low or No ERBB2 Expression Treated With Targeted Therapies Plus Endocrine Therapy

Abstract: ImportanceApproximately 45% to 60% of hormone receptor (HR)–positive metastatic breast cancer (mBC) shows a low-level expression of ERBB2. Low ERBB2 expression is defined as ERBB2 immunohistochemical expression of 1+ or 2+ with a negative ERBB2 amplification by in situ hybridization. The efficacy of the antibody-drug conjugate trastuzumab deruxtecan in low-ERBB2, HR-positive mBC has been practice changing. However, there are conflicting data on the prognostic value of low ERBB2 expression in HR-positive mBC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Nine studies encompassing a total of 2705 patients were included in the analyses. The four studies were conducted in the first line [ 18 , 23 25 ], while mixed cohorts were present in five studies [ 17 , 19 , 26 28 ]. Five studies were multicenter, and single-center data were reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies encompassing a total of 2705 patients were included in the analyses. The four studies were conducted in the first line [ 18 , 23 25 ], while mixed cohorts were present in five studies [ 17 , 19 , 26 28 ]. Five studies were multicenter, and single-center data were reported in four studies.…”
Section: Resultsmentioning
confidence: 99%
“…Six of nine studies reported no association between the HER2-low status and PFS with CDK 4/6 inhibitors [ 17 , 23 25 , 27 , 28 ]. In the pooled analysis of nine studies, the risk of progression and/or death was higher in patients with the HER2-low tumors compared to HER2 zero (HR: 1.22, 95% CI 1.10–1.35, p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have highlighted the complexity of this task, which is influenced by various factors including cancer type, clinical stage, therapeutic interventions, nursing care, unexpected comorbidities, and other non-cancer related illnesses that may interplay [3][4][5][6] . Furthermore, the gene expression plays a crucial role in predicting cancer patient prognosis, such as HER2, VEGF, Ki67, etc [7][8][9][10][11][12] . Nevertheless, there is still a need for further improvement in prognostic accuracy to better inform treatment decisions and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Endocrine therapy is a fundamental component in the management of hormone receptor-positive breast cancer, with the primary objective of inhibiting the proliferative influence of estrogen and progesterone on the cancer cells [22]. Widely utilized pharmaceutical agents such as tamoxifen and aromatase inhibitors have effectively diminished recurrence risk and enhanced survival outcomes [23]. The selection and duration of this therapeutic approach are contingent upon the unique characteristics of the cancer and the menopausal status of the patient, emphasizing the necessity for individualized treatment plans in the comprehensive management of breast cancer [24].…”
Section: Introductionmentioning
confidence: 99%
“…The Oncotype DX test, a genomic assay, quantifies the expression of 21 genes in tumor tissue, producing a RS that stratifies patients into low (<18), intermediate (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and high (>31) risk of recurrence categories. This RS guides adjuvant therapy decisions, aiming to personalize treatment approaches based on genetic risk profiles.…”
Section: Introductionmentioning
confidence: 99%